Efektivitas Media Google Classroom Pada Proses Pelajaran Instalasi Penerangan Listrik Sekolah Menengah Kejuruan - Adha Lilhamdi; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to determine the effectiveness of the google classroom media on the subject of electric lighting installation at SMK Negeri 5 Padang. Student learning outcomes are still low because students cannot do learning directly. Therefore, it is necessary to conduct research with the application of google classroom learning media to see the effectiveness of student learning outcomes. This research uses descriptive research. This study tries to provide a systematic description of the facts and true nature of a particular population. The subjects of this study were students of class XI TITL Electrical Engineering Department at SMK Negeri 5 Padang who were registered in the 2021/2022 academic year and totaled 30 students. The data collection used in this study was in the form of providing material in 2 meetings with one basic competency and providing an evaluation. After learning, students will be given post-test questions to find out whether the learning is effective or not by comparing the results of the post-test scores with the KKM in the school. Based on the post-test data analysis of 30 students, the average post-test score was 82.83, 27 students completed, and 3 students were below the KKM. Based on this score, 90% of students scored higher than the KKM, and obtained classical mastery of students in the very effective category. So in terms of classical completeness, online learning using the Google Classroom application is categorized as very.